Funds use and efficiency of artisanal fishing in Oguta, Imo State, Nigeria - Akpan N. Russell; Bassey Uyouko; Ekpenyong Iyaji (Advances in Aquaculture and Fisheries Management, 2014)
This study determined the cost-returns and the efficiency of resources used in artisanal fishing by fishers in Oguta Local Government Area of Imo State Nigeria. Data used for the study was obtained from primary and secondary sources using a multi-stage random sampling technique. In the first stage, 10 villages out of the 27 villages in Oguta were selected at random. In the second stage, 4 fishers were selected from each of the villages making a total of 40 respondents in Oguta Ameshi. Similarly, 60 respondents were selected from Ubi, which is made up of 27 farm settlements (Egwes). This brought the total sample size to 100. The result showed that the total revenue was N354, 530.00 with a total variable cost of N160, 677.23. The gross margin realized was N193, 852.77 with a net profit of N161,444.52. The study shows that the revenue from artisanal fishing was best estimated using the linear functions, which explained 51.5% of the total variations. The research identified that artisanal fishing is profitable and all the factors employed were inefficiently utilized. This suggests that higher profit and yields could be attained by efficient allocation of the employed resources which is vital to the sustainability of fishing in Nigeria.